2011
DOI: 10.2202/2152-2812.1004
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Cost Analysis for Drinking Water Standards: Efficiency, Equity, and Affordability Considerations in Small Communities

Abstract: The federal Safe Drinking Water Act (SDWA), as amended in 1996, enables benefit-cost analysis (BCA) to be used in setting federal drinking water standards, known as MCLs. While BCAs are typically conceived of as a tool to inform efficiency considerations by helping to identify MCL options that maximize net social benefits, in this paper we also illustrate how important equity and affordability considerations can be brought to light by suitably applying BCAs to drinking water regulations, especially in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…For drinking water regulations, however, the same households that benefit from the regulation typically bear the full compliance cost. In this context, Raucher et al, (2011) argue that negative health impacts arising from regulatory costs may appreciably offset the risk reduction of the drinking water regulation itself. That is, increasing the cost of water service to a distressed household will increase the likelihood that the household will forego some other health related necessity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For drinking water regulations, however, the same households that benefit from the regulation typically bear the full compliance cost. In this context, Raucher et al, (2011) argue that negative health impacts arising from regulatory costs may appreciably offset the risk reduction of the drinking water regulation itself. That is, increasing the cost of water service to a distressed household will increase the likelihood that the household will forego some other health related necessity.…”
Section: Discussionmentioning
confidence: 99%
“…These questions address a household's ability to meet essential expenses such as rent, utility, and medical bills; the ability to see a doctor or dentist as needed; and the adequacy of food availability. Based on the Bauman (1998) SIPP analysis, and similar hardship or financial distress studies, a hierarchy of household necessities can be constructed as shown in Figure 1 Raucher et al (2011), based on Bauman (1998Bauman ( , 1999, Energy CENTS Coalition (1999), and Boushey et al…”
Section: Health-health Analysis and Standard Settingmentioning
confidence: 99%
“…Doctrinally, the proposal reiterated the Agency's longstanding view that economic feasibility is limited to "what may reasonably be afforded by large metropolitan or regional public water systems" (p. 10682), thus leaving unaddressed the economic inefficiency and inequity discussed in Section 3. The proposed revision was widely criticized by public commenters (USEPA, 2006c) and subsequently by others (Rubin et al, 2007;Crawford-Brown et al, 2009;Raucher et al, 2011;U.S. Conference of Mayors et al, 2013a;U.S.…”
Section: Usepa's Proposed Revision To the Affordability Doctrinementioning
confidence: 99%
“…Balancing affordability in small water systems with system sustainability has proved to be difficult. Despite extensive work at all levels of industry and government in the United States, the policy issue of affordability and sustainability has not been fully resolved (Raucher et al 2011). The same difficulty applies to Canada as well.…”
Section: Sizes Of Drinking Water Systems Regulated By Alberta Environmentioning
confidence: 99%